Money and pay-as-you-go pension - Masaya Yasuoka (Economies, 2018)
This paper presents examination of how a pension policy affects income growth and the inflation rate in a utility model. Even if the contribution rate of pension increases because of an aging society, an aging society increases income growth and the inflation rate. Moreover, this paper presents examination of the optimal growth rate of the money supply. Because of the pension policy, the optimal growth rate of money stock changes. This result is intuitive because a pay-as-you-go pension changes capital accumulation. Therefore, the income growth rate should be changed to raise the welfare of all generations.
Keywords: H55; E52; O42; J11; 330; income growth; pay-as-you-go pension; monetary policy; fewer children